ANALYSIS OF ACTIVITY BASED COSTING AS THE BASIS FOR INPATIENT SERVICES TARIFF AT INTAN MEDIKA LAMONGAN HOSPITAL - Munaa, Nihayatul; Rahmawati, Nahardian Vica; Nurdiana, Fara; Kusdiyana, Ari; Kusbiantoro, Dadang; Sholihah, Enny Mar’atus (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2024)
Activity Based Costing is a cost assignment system based on the activities carried out by the company to produce products. The aim of this research is to find out and obtain information about calculating and comparing prices for inpatient room rates using conventional cost calculation methods with the ABC method. This is the quantitative descriptive research involves conducting interviews with the person in charge of the VIP inpatient room and financial department who relates to the research data. The results of the research show that the calculation of inpatient service rates using the Activity Based Costing method for the VIP class is IDR 160,499. From these results, when compared with the tariff used by Intan Medika Hospital of IDR 266,000, the Activity Based Costing method provides cheaper results with a difference of IDR 105,501. So by reducing rates according to the Activity Based Costing method, Intan Medika Hospital can expand its market because if it uses more appropriate prices and provides good quality, customers will choose to use Intan Medika Lamongan Hospital, so that Intan Medika Lamongan Hospital can increase the occupancy of VIP inpatient room and have a long-term profits.